Thermodynamic, diffusion and precipitation behaviors in Cu–Ni–Si–Co alloys: Modeling and experimental validation - Haoyue Ling; Ying Tang; Jing Zhong; Xiangpeng Meng; Min Zhang; Lijun Zhang (Journal of Materials Research and Technology)
Aging precipitation is an important process that affects the mechanical and electrical properties of Cu alloys. Quantitative prediction of microstructure evolution during aging process is crucial for controlling their performance. The mean field method is an important means of precipitation simulation, but its reliability strongly depends on the input of accurate thermodynamic and kinetic data. In this paper, a comprehensive study on the thermodynamic, diffusion, and precipitation behavior of Cu–Ni–Si–Co alloy was conducted by combining modeling and experimental techniques. Firstly, a thermodynamic database of quaternary Cu–Ni–Si–Co system was constructed and verified by key experiments. Then, HitDIC software was used to establish an atomic mobility database by incorporating experimental quaternary diffusion properties, allowing for accurate determination of interdiffusion coefficients. After that, a quantitative precipitation simulation framework was developed and applied to Cu–Ni–Si–Co alloys. The simulated volume fractions of (Ni,Co)2Si precipitates in different quaternary alloys along with the time agree well with the experimental data. It is anticipated that the presently obtained quantitative composition-process-microstructure relation can be directly used for efficient design of Cu–Ni–Si–Co alloys, and the developed approaches for establishing thermodynamic/kinetic database as well as quantitative precipitation simulation framework is generally applicable to other multicomponent alloys.